Penerapan Model Example Non Example Untuk Meningkatkan Hasil Belajar Siswa Kelas 5 MI Muhammadiyah Pabelan - Fitriyati, Fina (Prosiding University Research Colloquium, 2021)
The purpose of this research is to omprove the student’s learning skills by applying the Non Example Learning Model. The research method used is Class Action Research (PTK) consisting of two cycles where each cycle has a planning, action, observation, and reflection stage. This research involves seven fifth grade elementary students. Based on observations and tests on cycle 1 there is an increase. The highest score after the treatment done on cycle 1 was 85 and the lowest score 71 with an average of 76.85. Whereas the initial results were the highest score is 75 and the lowest score is 60 with a flat rate of 66.57. While the results at cycle stage 2 are 90 highest and 78 lowest with a flat rate of 82.28. The first half of the score is the highest 80 and the lowest 70 with a flat 75.71. So it can be concluded that the model learning Non-Example can increase student learning outcomes.